Psychodynamic Interpretation of Ritual in the Structure Obsessive-Compulsive Disorder - Mikayelyan, Erik (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
As it is known, in psychoanalysis as well as in analytical psychology, the ritual is seen as a symptom of how repetitive actions or certain forms of behavior, latent containing a therapeutic function. In the psychoanalytic paradigm of ritual, it is also considered as a substitute for the sexual or aggressive activity of the person. a criterion stands in psychoanalysis, according to which, an obsessive ritual becomes in those cases where the impossibility of its fulfillment in the person creates a feeling of anxiety or fear of waiting for something tragic. This distinguishing criterion, despite its obviousness, is still somewhat abstract or devoid of objectivity. While the ritual is complete, anxiety does not go away - so seems the criterion for distinguishing normal ritual of neurotic ritual.
Keywords: obsessive behavior, reaction formation, compulsions, rituals, obsessivecompulsive neurosis